Late La Tène and Early Roman textile tools from Dorno, Italy - Scansetti, Serena (Archaeological Textiles Review, 2020)
This paper presents late Celtic and Roman textile tools from the territory of Dorno, a small town in northern Italy. Sheep shearing and spinning are very well documented activities at this site with 21 pairs of iron shears and 88 clay spindle whorls recorded. These implements come from burial contexts dating from between the second century BCE and the first century CE. The spindle whorls show a great variety of shapes and weights, and, with their large number, they contribute to an understanding of the local economy. The association of textile tools with other burial goods, in both men’s and women’s graves, provides further information not only about the role of the textile industry within this community but also about social organisation and burial rituals.